2016
DOI: 10.1016/j.jpsychores.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric analysis of the Patient Health Questionnaire in Danish patients with an implantable cardioverter defibrillator (The DEFIB-WOMEN study)

Abstract: The unidimensionality and reliability of the Danish version of the PHQ-9 were confirmed. However, the associated consequences of the number of response options (3-point versus 4-point Likert scale) need to be further examined for the PHQ-9 both as a screening tool and outcome measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…All items are scored on a 0- to 3-point scale with a total score of 0-27, and higher scores indicated more severe depression. One study of the Danish version confirmed unidimensionality and reliability but suggests collapsing the two middle response categories [38]. However, the scale used in the Internetpsykiatrien clinic followed the original structure of the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…All items are scored on a 0- to 3-point scale with a total score of 0-27, and higher scores indicated more severe depression. One study of the Danish version confirmed unidimensionality and reliability but suggests collapsing the two middle response categories [38]. However, the scale used in the Internetpsykiatrien clinic followed the original structure of the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…In order to advance the field and enhance the quality of care for patients with CVD we need to: Implement screening of patients in clinical practice in order to identify the subset of patients at risk. We have core questions available for the physicians to include in their interview 36 and full, standardised and validated questionnaires 3741 to make a more extended assessment that has been shown to predict patient and clinical outcomes. Start incorporating psychosocial factors into CVD risk prediction models at an equal level to standard risk factors, such as age and smoking, as psychosocial factors are not only risk modifiers but also independent risk factors for poor patient and clinical outcomes. 36 Design effective interventions that target psychosocial risk factors and that use a more precision medicine approach rather than a ‘one-size-fits-all’ approach.…”
Section: Recommendations and Future Perspectivesmentioning
confidence: 99%
“…Implement screening of patients in clinical practice in order to identify the subset of patients at risk. We have core questions available for the physicians to include in their interview 36 and full, standardised and validated questionnaires [37][38][39][40][41] to make a more extended assessment that has been shown to predict patient and clinical outcomes. .…”
Section: Recommendations and Future Perspectivesmentioning
confidence: 99%
“…Because of the ceiling effect, a patient with MDD seen in primary care who continues to work would score similarly to a depressed patient who is hospitalized because of difficulties with self‐care. While there are several studies of the PHQ‐9 using an item response theory approach, these have been of heterogeneous non‐depressed psychiatric, medical or community samples. We are unaware of any studies evaluating the performance of the PHQ‐9 items in a sample of depressed patients presenting for treatment.…”
Section: Severity Of Depressionmentioning
confidence: 99%